Process for Leveraging Enterprise Architecture in Information Systems Strategic Planning: A Case of Developing a Strategy and Master Plan for a National Integrated Health Laboratory Information Management System in Uganda - Agnes Nakakawa; Daniel Kasule; Michael Kasusse; Gaspard Guma; Steven Aisu; Patrick A. Ogwok; Hakim Sendagire (Complex Systems Informatics and Modeling Quarterly)
Effective alignment of institutional processes with digital technologies is imperative for enterprises, including those in healthcare. Unfortunately, in the context of health laboratories, the scope and complexity of existing digital health interventions has not allowed incorporation of all data and information needs for all core functions of the laboratory subsector. Besides, several operational and management issues still hinder the effective management of information on laboratory services at the health facility, sub-national, and national levels in low-income countries such as Uganda. Although approaches that support implementation of digital health interventions exist, there is still limited technical guidance on the strategic planning and implementation of complex systems such as a nation-wide integrated Health Laboratory Information Management System (HLIMS). Therefore, this article demonstrates how the strategic planning process of such systems can be strengthened by adopting the thinking pattern of enterprise architecture, as a holistic approach for aligning business processes with digital technologies. It specifically presents a process for leveraging Enterprise Architecture in Information Systems Strategic Planning (EAISSP). The process was instantiated in Uganda’s health laboratory subsector, by using it to formulate an architecture-oriented information systems strategy; and the strategy then guided the design of a master plan for a national integrated HLIMS and its implementation plan. Although EAISSP was tested in the context of the laboratory subsector, it can be contextualized to support other efforts like developing a national e-health strategy or information systems strategy of an enterprise in another sector.